LY6D is crucial for lipid accumulation and inflammation in nonalcoholic fatty liver disease - Jibeom Lee; Hyeonhui Kim; Yun-Won Kang; Yumin Kim; Moon-young Park; Ji-Hong Song; Yunju Jo; Tam Dao; Dongryeol Ryu; Junguee Lee; Chang-Myung Oh; Sangkyu Park (Experimental and Molecular Medicine, 2023)
Abstract Nonalcoholic fatty liver disease (NAFLD) is a serious metabolic disorder characterized by excess fat accumulation in the liver. Over the past decade, NAFLD prevalence and incidence have risen globally. There are currently no effective licensed drugs for its treatment. Thus, further study is required to identify new targets for NAFLD prevention and treatment. In this study, we fed C57BL6/J mice one of three diets, a standard chow diet, high-sucrose diet, or high-fat diet, and then characterized them. The mice fed a high-sucrose diet had more severely compacted macrovesicular and microvesicular lipid droplets than those in the other groups. Mouse liver transcriptome analysis identified lymphocyte antigen 6 family member D (Ly6d) as a key regulator of hepatic steatosis and the inflammatory response. Data from the Genotype-Tissue Expression project database showed that individuals with high liver Ly6d expression had more severe NAFLD histology than those with low liver Ly6d expression. In AML12 mouse hepatocytes, Ly6d overexpression increased lipid accumulation, while Ly6d knockdown decreased lipid accumulation. Inhibition of Ly6d ameliorated hepatic steatosis in a diet-induced NAFLD mouse model. Western blot analysis showed that Ly6d phosphorylated and activated ATP citrate lyase, which is a key enzyme in de novo lipogenesis. In addition, RNA- and ATAC-sequencing analyses revealed that Ly6d drives NAFLD progression by causing genetic and epigenetic changes. In conclusion, Ly6d is responsible for the regulation of lipid metabolism, and inhibiting Ly6d can prevent diet-induced steatosis in the liver. These findings highlight Ly6d as a novel therapeutic target for NAFLD.